A finite element analysis of the carpal arch with various locations of carpal tunnel release - Yu, Lu; Jia, Jingyi; Lakshminarayanan, Kishor; Li, Yiming; Gan, Yaokai; Yao, Yifei (Frontiers in Surgery, 2023)
Objective The purpose of this study was to investigate the effects of the location of transverse carpal ligament (TCL) transection on the biomechanical property of the carpal arch structure. It was hypothesized that carpal tunnel release would lead to an increase of the carpal arch compliance (CAC) in a location-dependent manner. Methods A pseudo-3D finite element model of the volar carpal arch at the distal carpal tunnel was used to simulate arch area change under different intratunnel pressures (0–72 mmHg) after TCL transection at different locations along the transverse direction of the TCL. Results The CAC of the intact carpal arch was 0.092 mm2/mmHg, and the simulated transections ranging from 8 mm ulnarly to 8 mm radially from the center point of the TCL led to increased CACs that were 2.6–3.7 times of that of the intact carpal arch. The CACs after radial transections were greater than those ulnarly transected carpal arches. Conclusion The TCL transection in the radial region was biomechanically favorable in reducing carpal tunnel constraint for median nerve decompression.